Physico-chemical and heavy metals evaluation of the groundwater for the irrigation purpose with the water quality index studies at the Ratnagiri District, Maharashtra, India (International Journal of Food and Nutritional Sciences, 2022)
Groundwater sources are widely used for domestic and agricultural purposes by human beings and Water Quality Index (WQI) quantifies the suitability for the use. Although, groundwater resources are getting polluted by the various anthropogenic activities. Ratnagiri is an urbanising city and polluting activities are increasing nowadays. The study area chosen is from a 74 km stretch of coastal areas at the Ratnagiri district, Maharashtra, India. A total of 25 no. of samples from different locations were collected for the physicochemical, heavy metals analysis and water quality index (WQI) have dominantly carried out for the suitability of drinking and irrigation purposes in the present study. Water analysis methods are followed from the bureau of Indian standards (BIS) and world health organization (WHO) guidelines and compared accordingly to the BIS (ISO10500:2012) permissible limits. Chloride (Cl), Total dissolved solids (TDS), and Total Hardness (TH) values were above the permissible limit during the pre-monsoon period (PRM). Lead and Zinc values have increased (2 locations), which may lead by continuous human interventions. From the piper-trilinear diagram, it was observed that most of the samples are mixed type with Ca2+ as predominant cation, especially in the pre-monsoon period. According to the permeability index (PI), sodium percentage (SSP), Kelly’s Ratio (KR), Sodium Absorption Ratio (SAR), Magnesium Hazard (MH), Percent Sodium (NA%), and Residual Sodium Carbonate (RSC) all the samples during PRM and post-monsoon period (POM), were found to be good for the irrigation purpose. As per the WQI, excellent water quality during PRM is observed only at one location (1 sample of 25) and during POM it has increased by 48 % (12 samples of 25), showing that the groundwater quality has increased after the monsoon. A suggestion is that to minimize pollution of groundwater, rainwater harvesting be preferably done.